Diagnostic and propaedeutic updates in brain death: A literature review (Research, Society and Development, 2023)
Brain death (BD) is described as the irreversible cessation of cortical cerebral and brain stem functions, which implies the impossibility of maintaining life without artificial support. In 2017, the Federal Council of Medicine (CFM) updated the diagnostic criteria for ME, criteria in which the mandatory professional qualifications, clinical diagnostic criteria, interval between evaluations and complementary exams for brain function are changed. An integrative literature review was prepared regarding national updates on brain death, including the diagnostic and propaedeutic approach, carried out in the databases PubMed, Web of Science, Scopus, Cochrane Database of Systematic Reviews (CDSR), EBSCOhost, Virtual Library of Health (VHL) and Scientific Electronic Library Online (SCIELO). It was seen that, in the presence of brain injury, the cause must be known, and there must be no treatable factors that could confuse the diagnosis of BD. Furthermore, the patient must receive treatment and be observed in a hospital environment for a minimum period of six hours, except when the cause is primary hypoxic-ischemic encephalopathy, in which case observation must be extended to 24 hours. It is mandatory to carry out at least two clinical examinations that confirm the absence of perception and the lack of brain stem function, followed by an apnea test that proves the absence of respiratory movements after maximum stimulation of the respiratory centers, in addition to a complementary examination to confirm the absence of brain activity. Furthermore, one of the trained doctors must be a specialist in one of the following areas: intensive care medicine, pediatric intensive care medicine, neurology, pediatric neurology, neurosurgery or emergency medicine, or have at least one year of experience in treating comatose patients, following the CFM guidelines. Adequate communication and completion of the ME Declaration Form are the responsibility of the medical team that performed the diagnostic procedures.